2016
DOI: 10.2134/jeq2015.06.0261
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Predict Uptake of Trace Organic Compounds by Plants

Abstract: Application of manure, biosolids, and recycled wastewater to croplands could be a potential pathway through which trace organic compounds (TOrCs) may be taken up by food crops. We present a framework to prepare a short list of TOrCs for detailed risk assessment and evaluation in terms of bioaccumulation. The framework was modified from Lipinski's method to predict drug permeability based on four critical properties: (i) molecular weight (MW); (ii) lipophilicity (expressed as log, the octanol-water partition co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Similarly Shenker et al (2011) found the largest concentrations in the leaves followed by the concentrations in the roots, stems, and fruits of cucumber plants. The high accumulation in the leaves of green pea plants is associated with the transpiration stream and not the restricted transfer of neutral molecules of low MW, lipophilicity, and number of H-bonds (Kumar and Gupta, 2016) through the plant bodies (e.g., Goldstein et al, 2014;Hurtado et al, 2016;Kodešová et al, 2019a, b;Malchi et al, 2014;Montemurro et al, 2017;Mordechay et al, 2018;Shenker et al, 2011, Winker et al, 2010Wu et al, 2013) due to a passive diffusion through lipid bilayer membranes (Chuang et al, 2019). The lower accumulation in the pods is explained by the significantly shorter exposure to the contamination and a lower transpiration of pods in comparison to that in the leaves.…”
Section: Bioaccumulation Of Pharmaceuticals and Their Metabolites -Nementioning
confidence: 99%
“…Similarly Shenker et al (2011) found the largest concentrations in the leaves followed by the concentrations in the roots, stems, and fruits of cucumber plants. The high accumulation in the leaves of green pea plants is associated with the transpiration stream and not the restricted transfer of neutral molecules of low MW, lipophilicity, and number of H-bonds (Kumar and Gupta, 2016) through the plant bodies (e.g., Goldstein et al, 2014;Hurtado et al, 2016;Kodešová et al, 2019a, b;Malchi et al, 2014;Montemurro et al, 2017;Mordechay et al, 2018;Shenker et al, 2011, Winker et al, 2010Wu et al, 2013) due to a passive diffusion through lipid bilayer membranes (Chuang et al, 2019). The lower accumulation in the pods is explained by the significantly shorter exposure to the contamination and a lower transpiration of pods in comparison to that in the leaves.…”
Section: Bioaccumulation Of Pharmaceuticals and Their Metabolites -Nementioning
confidence: 99%
“…In addition to charged species and hydrophobicity, the bioaccumulation of pharmaceuticals could also be affected by chemical molecular weight (MW), plant physiology, metabolism, exposure time, and plant growth rates, etc. For example, MW is considered as another factor that associate with the membrane permeability (Kumar and Gupta, 2016;Topp et al, 1986). Studies on diffusion have indicated that the compounds with MW > g/mol have the restricted membrane permeability (Camenisch et al, 1998), while the compounds with MW > 1000 g/mol are impossible to be absorbed by cells (Sanderson et al, 2004).…”
Section: Relationship Between Pharmaceutical Properties and Root Uptakementioning
confidence: 99%
“…Such problems are mitigated in the model developed in this study, which can be used in various applications, such as phytoremediation involving uptake and metabolization processes of toxic compounds from contaminated soils (e.g., Ouyang, 2002), pesticides fate assessment (e.g., Legind et al, 2011), remediation of contaminated groundwater plumes (e.g., Hong et al, 2001), assessment of salinity in agricultural arid areas (e.g., Trapp et al, 2008), and air pollution removal by urban vegetation (e.g, Yang et al, 2008). To further extend the range of the model applicability, future research should focus on the modification of the model structure to consider DPU of electrolytes and refine the description of the root uptake mechanism of large molecules (Kumar & Gupta, 2016).…”
Section: Integrated Soil-plant Modelmentioning
confidence: 99%